The First Mom and Dad - Dania Deji (Literamed publications, 2009)
God warned the first Mom and Dad against eating the fruit of the tree of The Knowledge of Good and Evil but the serpent comes around and a happy existence turns sour.
Keywords: Non Fiction / Religion / Christianity / Bible Stories